Online Learning: A 21st Century Approach to Education With Specific Emphasis on E-Learning Platforms With Reference to India - Sehrawat, Sweta (Digital Repository of Theses, 2024)
Online learning, particularly in the twenty-first century, has become a significant paradigm shift in education, introducing new techniques of teaching and learning. The goal of this study is to investigate the situation of online education in India, with a focus on e-learning platforms. The research conducts a detailed investigation of the issues students have while using these platforms, the variety of online course topics, the competitiveness of e-learning platforms, the benefits of online learning, and ways for overcoming the challenges these platforms face. With the success of online learning as the dependent variable, the study employs a mixedmethods approach that includes surveys, interviews, and a literature review to investigate the relationship between independent variables such as the difficulties in implementing e-learning platforms, their efficacy, the benefits of online learning in the modern world, and the impact of e-learning platforms on the quality of education in India. The findings reveal that, although there are still challenges to overcome, such as infrastructural shortages and technological limitations, e-learning platforms have enormous potential for enhancing student outcomes. The study stresses how important it is to understand and address these difficulties in order to maximize the benefits of online learning. Stakeholders such as lawmakers, educators, and platform developers are offered advice on how to create an environment that would promote the growth and effectiveness of online education in India. This research contributes to the existing body of knowledge by providing light on the nuances of online learning in the Indian context and giving practical recommendations for addressing challenges and utilizing the potential of e-learning platforms to alter education in the twentyfirst century.